Factors Associated With Loss to Follow Up During Treatment of Latent Tuberculosis Infection in Children Under 5 Years of Age in Sabah, Malaysia - Sheila Miriam Mujin; Richard Avoi; Roddy Teo (Universiti Putra Malaysia, 2023)
Loss to follow up remains one of the main problems in the treatment of latent tuberculosis infection (LTBI) in the state of Sabah, Malaysia. This study aims to identify the risk factors for loss to follow-up among LTBI treated TB contacts in children under 5 years of age, who did not complete 180 dosages of treatment within 6 to 9 months. Methods: This retrospective cohort study used anonymised data taken from the Malaysia national case-based TB registry (MyTB) between 2017 and 2019. To identify factors related with loss to follow-up, a logistic regression analysis was performed. Results: Of the 1334 treated LTBI cases, 10.4% were loss-to-follow-up. The mean age of study participants was 2.3 years, with 50.2% males. Factors associated with loss to follow-up include index-contact relationship i.e., Extended family (aOR = 1.82, 95% CI = 1.19, 2.77) and PTB index in whom the treatment outcome is loss to follow up (aOR = 4.84, 95% CI = 1.96, 11.95). Rural living was associated with less loss to follow (adjusted odds ratio (aOR) = 0.40, 95% confidence interval (CI) = 0.26, 0.61). Conclusion: Despite commendable efforts, the problem of loss to follow during LTBI treatment in children persisted. In spite of the inherent limitations of the study, the associated factors identified in this study can be used as a basis for future initiatives to strengthen LTBI management.